Reciclagem de cavacos de ligas de alumínio 7050-T7451 utilizando conformação por spray e tratamentos termomecânicos - Hyodo, Alexandre (2012)
The aim of this work is to conjugate a sort of known processing techniques in to a machining chips recycling route. These are generate during airframe primary parts from AA 7050-T7451, purchased according to AMS 4050H. The main processes assessed in this work were sprayforming, thermomechanical processes and heat treatments. According to the gathered data, the homogenization heat treatment after sprayforming has improved the investigated material properties significantly. The use of hot torsion test was fundamental in order to define the best processing route in order to define a refined microstructure. Beside the hot torsion tests survey, a methodology of experimental data treatment and analysis was developed and used accordingly. And based on these analyses, a new extrusion matrix was designed and manufactured. The new average grain size about 4.0 m obtained has presented good correlation with the size predicted by the method developed. Tensile test data has presented higher than the values specified in AMS 4050 H. Preliminary fatigue data has showed a dispersion within the MMPDS-06 (former MIL-HDBL-5), for similar testing condition, and fulfill the AMS 4050H fatigue requirements.